Joint Investigation Team in the fight against human trafficking: The Paraguay-Spain experience (Legal journal - Research in Legal and Social Sciences, 2020)
This paper aims to comprehend the meaning of Joint Investigation Team, JIT onwards. To achieve that, this study describes the concept, characteristics, and how they are put together. Also, it details the benefits obtained after its implementation as an effective tool in the fight against human trafficking. The paper also highlights the valuable work between the countries that enable to counteract this type of crime, whose victims are in vulnerable situations. Human Trafficking is a transnational crime that affects more than one State, the fight against it requires machanisms that enable to work in teams made up of justice workers who take action against this complex type of crime. Currently, the Specialized Division for the fight against Trafficking in Humans has conducted several joint operations with spanish authorities, within the framework of a JIT, that delivered positive results, some of these operations were the toblerone, chipa, among others, which are described in this paper. These experiences are the evidence for the need to know and apply this type of tools for the prosecution of the crimes.
Keywords: Human Trafficking; Joint Investigation Teams; victims